STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA KARYAWAN DI ERA TRANSFORMASI DIGITAL: SEBUAH STUDI LITERATUR - Budiman (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2026)
The research is based on the current situation in 2026, where digital transformation has reached its peak, where the integration of Artificial Intelligence (AI) and automation has become the operational standard for organizations. However, the main challenges that arise are the skills gap and cultural resistance within the organization. Human Resource Management (HRM) is required to formulate new strategies to ensure optimal employee performance amidst disruptive technological changes. The purpose of this study is to analyze the most effective HRM strategies for improving employee performance in the era of digital transformation and to identify the determinants that support the successful implementation of technology in people management. Method this study used a qualitative approach with library research. Data were obtained through a literature search related to the study. Data analysis techniques involved data reduction, categorization, and theoretical synthesis to develop a new framework. The research findings indicate four main strategies for improving performance in the digital era: (1) Implementing Data-Driven HR through an AI-based e-HRM system; (2) Continuous competency development through personalized learning (micro-learning); (3) Transforming leadership into adaptive Digital Leadership; and (4) Creating a flexible work culture that prioritizes digital well-being. The synergy between technology and human aspects has proven to be a key factor that significantly increases productivity today. From this research, it can be concluded that digital transformation requires repositioning HR from an administrative function to a strategic partner. Employee performance in this era is highly dependent on an organization's ability to integrate technology into its work culture without neglecting employee mental well-being.